PEMANFAATAN TEKNOLOGI DALAM MANAJEMEN PEMBIAYAAN PENDIDIKAN DI SEKOLAH - NUR, ALFIAN FIKRI; NURFUADI, NURFUADI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
In the modern era like today, technology is no longer a foreign thing. In all fields, many technologies are created to facilitate humans in carrying out their activities. Including in the world of education, various innovations and technologies are created to facilitate and advance education. The use of technology in educational financing management in schools is also growing rapidly along with advances in information technology. This article aims to explore how technology can be used in managing educational funds in schools through a library research approach. This study examines various literatures that discuss the application of technology in financial management and financing in educational institutions. The results of the study show that technology, such as digital-based financial management information systems, financial reporting applications, and electronic payment methods, have been shown to increase efficiency, accountability, and transparency in the management of educational funds. In addition, technology also facilitates the involvement of stakeholders, including the government, schools, and parents of students, in monitoring and supervising the allocation of funds. This article concludes that technology has great potential in improving the quality of educational financing management in schools. ABSTRAKPada era modern seperti sekarang ini, teknologi merupakan hal yang sudah tidak asing lagi. Dalam semua bidang, banyak teknologi tercipta untuk memudahkan manusia dalam menjalankan kegiatannya. Termasuk dalam dunia pendidikan, berbagai inovasi dan teknologi tercipta untuk memudahkan dan memajukan pendidikan. Pemanfaatan teknologi dalam manajemen pembiayaan pendidikan di sekolah juga berkembang pesat seiring dengan kemajuan teknologi informasi. Artikel ini bertujuan untuk mengeksplorasi bagaimana teknologi dapat digunakan dalam mengelola dana pendidikan di sekolah melalui pendekatan penelitian kepustakaan (studi pustaka). Penelitian ini mengkaji berbagai literatur yang membahas penerapan teknologi dalam pengelolaan keuangan dan pembiayaan di institusi pendidikan. Hasil penelitian menunjukkan bahwa teknologi, seperti sistem informasi manajemen keuangan berbasis digital, aplikasi pelaporan keuangan, dan metode pembayaran elektronik, telah terbukti meningkatkan efisiensi, akuntabilitas, dan transparansi dalam pengelolaan dana pendidikan. Selain itu, teknologi juga memfasilitasi keterlibatan berbagai pihak, termasuk pemerintah, sekolah, dan orang tua siswa, dalam memantau dan mengawasi alokasi dana. Artikel ini menyimpulkan bahwa teknologi memiliki potensi besar dalam meningkatkan kualitas manajemen pembiayaan pendidikan di sekolah.